Anthropology as an inspiration to food studies: building theory and practice - Agnieszka Siewicz (AntropoWebzin, 2011)
The aim of this paper is to show the role of anthropological inquiry in the development of a new, interdisciplinary approach to food in culture - namely: food studies. Early anthropologists, for example, Bronislaw Malinowski and Edward Evans-Pritchard, stressed the social meaning of food while analyzing the outcome of their fieldwork. When the functional approach had been replaced by structuralism, the symbolic meaning of food was given priority. Therefore, Claude Lévi-Strauss constructed his famous culinary triangle to show the connection between culture and nature in human thought; however, the triangle was not based on his own fieldwork, but rather many examples from other works were used to support this theoretical approach. This paper shows that without the theoretical and practical contribution of these three anthropologists, the flourishing of food studies as a new discipline would have been seriously delayed.